Gastrostomy Tubes in Children with Nonambulatory Cerebral Palsy and Neuromuscular Scoliosis: An Enemy or an Ally? Current Concept Review - Shiver, Austin; Shaw, Kenneth; Murphy, Joshua; Fletcher, Nicholas (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Gastrostomy tubes or equivalent invasive nutritional support devices are an important component for maintaining appropriate nutrition for children with cerebral palsy who have oromotor dysfunction. Although these interventions have been shown to produce positive influences on the child’s health and nutrition status, they have also been associated with increased complication rates following spinal deformity surgery. Understanding the current status of the literature on this topic as well as the gaps in knowledge are crucial to gaining a thorough understanding of the role of these feeding devices in the postoperative complication profile for these at-risk patients and avenues for future research efforts.